Healthier vegetables through temperature stress? : a review of Brassica oleracea - Enocksson, Anna (SLU/Dept. of Biosystems and Technology (from 130101), 2013)
The objective of this report is to present a review of the studies which has been carried out up to days date concerning how temperature affects vegetables physiologically when it comes to their health inducing as well as quality reducing features. The essay therefore starts off with defining what is meant by the terms health promoting and quality reducing features. It then moves on to describe how different subspecies of Brassica oleracea, that is to say vegetables such as broccoli, cauliflower, Brussels sprouts and kale, is affected by temperature. B. oleracea was chosen because the species contains several commercially interesting subspecies and therefore provides a broad field even though only one species is assessed. Several of the subspecies have also been of special interest in the popular science in later years and have been said to be very healthy which makes them interesting for this thesis. Concerning temperature, focus is put mainly on temperature treatments during processing and cooking since this field has been studied more thoroughly. However, general temperature stress is also being discussed, both concerning pre- and postharvest conditions. The conclusions which can be made based on this report are that vegetables are physiologically very affected by temperature, and that temperature processing reduces the sensory quality of B. oleracea whereas it may actually enhance its health promoting effects, if the right cooking method is chosen. However, the content of these health promoting compounds varies greatly between genotypes within one subspecies which makes clear definitions essential.